Collective Bargaining in the Public Sector: The Effect of Legal Structure on Dispute Costs and Wages - Currie, Janet; McConnell, Sheena (American Economic Review, 1991)
This paper examines the impact of collective-bargaining legislation on dispute costs and wages using a panel of Canadian public-sector contracts. Our results suggest that policymakers designing collective-bargaining legislation face a trade-off between reducing dispute costs and increasing wages. Dispute costs are lower under compulsory arbitration than under the right to strike or when no collective-bargaining legislation exists. Hence, a switch to compulsory arbitration could potentially make both the union and the employer better off by reducing dispute costs. However, we find that wages are higher under compulsory arbitration than under other legal structures.